Safety and efficacy of Vectored thermal pulsation, Intense pulsed light, and Eyelid Warm compress therapies (VIEW) for meibomian gland dysfunction: Study design and baseline characteristics of a randomized controlled trial - Zhichao Hu; Hanson Yiu Man Wong; Emily Hoi Ying Chan; Eric Ka Ho Choy; Andy Chak Fung Ng; Xulin Liao; Fatema Mohamed Ali Abdulla Aljufairi; Jake Uy Sebastian; Kenneth Ka Hei Lai; Charlotte Yi Sum Poon; Wanxue Chen; Vanissa Wing See Chow; et al. (PLoS ONE, 2026)
Background Meibomian gland dysfunction (MGD) is one of the most prevalent chronic eye diseases, characterized by meibomian gland obstruction and abnormal meibum secretion both in quantity and quality. Objective To assess the efficacy and safety of vectored thermal pulsation (VTP), intense pulsed light plus meibomian gland expression (IPL + MGX), and eyelid warm compress (EW). Methods This is a 3-arm, assessor-masked, randomized controlled trial. 360 symptomatic mild to moderate MGD subjects would be recruited and randomized into 3 intervention groups. Subjects from Group-A, Group-B, and Group-C would be treated with one-session VTP (at baseline), four-session IPL + MGX (at baseline, month-1, month-2, and month-3 visits), and twice-daily EW for 15 months, respectively. All subjects would be prescribed topical artificial tears (Hypromellose, 0.3% w/v) to be used as frequently as needed from wash-out (1 month before baseline) to endpoint (month-15 visit). Subjects would be assessed 9 times throughout a total of 16-month study period. Five self-administered questionnaires would be collected each time in random order. Masked observers would conduct examinations using slit-lamp biomicroscopy, LipiView® II, and Keratograph 5M machines. The eye with worse MGD would be selected and analyzed as the study eye. Tear film break-up time (TFBUT) at month-6 and month-15 visits are the primary outcomes. Results 374 subjects were enrolled and randomized into three groups, and 372 subjects (aged 54.4 ± 14.7 years) were finally analyzed. The mean of TFBUT time at baseline was 3.1 ± 1.7 seconds. Conclusion This is the first head-to-head comparison of three physical treatments for mild to moderate MGD on their therapeutic efficacy, safety, longevity and compliance in a randomized controlled trial setting.